Wound Complications in Head and Neck Squamous Cell Carcinomas After Anti–PD‐1 Therapy. (10th May 2019) - Hwang, Victoria; Mendez, Eduardo; Chow, Laura Q. M.; Futran, Neal David; Andersen, Peter; Li, Ryan; Divi, Vasu; Rodriguez, Cristina P.
Abstract : Immune checkpoint inhibitors have demonstrated activity in recurrent/metastatic head and neck squamous cell cancer, but less is known regarding their long‐term sequelae. We describe four patients who, after complete responses to anti–PD‐1 therapy, developed complications requiring surgical intervention. Patient 1 is a 57‐year‐old female whose marked tumor regression exposed some mandibular hardware. Patient 2 is a 39‐year‐old male who developed an ulcerated buccal lesion with exposed mandible. Patient 3 is a 66‐year‐old male with craniofacial osteoradionecrosis. Patient 4 is a 71‐year‐old male who developed an exposed and fractured mandible. All patients successfully underwent surgical intervention and remain disease free. Laryngoscope, 129:E428–E433, 2019